Changes in Rumen Parameters and Microbial Communities Over Inclusion Crud Glycerin in Goat Diet - Mani, AMM (Journal of the Hellenic Veterinary Medical Society, 2025)
Performance and ruminal parameters (pH, NH3 and volatile fatty acid) and microbial community of Twenty-four male goats (19.5 ± 2.2 kg BW and 120.0 ±10 days of age) fed diets containing crud glycerin (CG) in replacement of corn were investigated. Goats were distributed in a completely randomized design with three levels of replacement of corn by CG: 0, 100, 150 g/kg of dry matter with six replications, and kept individually in separate yards, experimental diets were formulated to be isonitrogen (CP content 14.5%), isoenergy (ME content 2.19 Mcal/kg) and the basal diet was composed of Alfalfa hay (300 g/kg) and concentrate (700 g/kg) containing corn and soybean for 60-days period. No effect on performance trails (final BW, and total gain) was observed, and there was a trend for Final weight (29.8 ±1.8 and 29.6±1.7) to be upper for CG inclusion groups than Control. No significant differences on DM intake was observed, while improved FCR by (7.46 ±0.32, 6.93 ±1.7 and 6.79 ±1.7) in treated groups. Ruminal pH and ammonia was decreased for goat fed the CG diet. There is significantly (P ≤ 0.05) increase in propionic and butyric acid content in line with the higher level of CG provision, unlike acetic acids, which shown a difference significantly (P ≤ 0.05) decrease compared with control groups. isobutyrate, valerate, and isovalerate concentrations and acetic acid to propionic acid ratio (A/P) were not affected by the different levels of CG. Minor changes in microbial community profile reduction were observed. The relative abundance of total bacteria (p = 0.032) and Fibrobacter succinogenes (p = 0.021) was lower in the treated groups, whereas the relative abundance of methanogenic Archea (p = 0.018) and protozoa (p = 0.028) was higher in the control group. In conclusion, the inclusion of CG in goat diet, causes shifts in the rumen microbiota and fermentation by increasing the formation of propionic and butyric acid content in line with the higher level of CG provision, unlike acetic acids.